Factor the trinomial `x^2 + 6x + 5`

`(x+5)(x+1)=0 `

Set each of the factors of the left-hand side of the
equation equal to `0` .

`x+5=0`

`x+1=0 `

Since `5` does not contain the variable to solve for, move it to the
right-hand side of the equation by subtracting `5` from both
sides.

`x=-5 `

`x+1=0 `

Set each of the factors of the left-hand side of the
equation equal to `0` .

`x=-5 `

`x+1=0 `

Since 1 does not contain the variable to solve for, move it to the
right-hand side of the equation by subtracting `1` from both
sides.

`x=-5 `

`x=-1`

The complete solution is the set of the individual
solutions.

`x=-5,-1`

Solve `x^2 + 6x + 5 = 0` .

Factor the quadratic.

`x^2 + 6x + 5 = 0`

`(x+5)(x+1) = 0`

Using the zero product property, set each factor equal to zero and solve.

`x+5 = 0` and `x+1 = 0`

`x = -5` and `x = -1`

**The solutions are x = -5, -1.**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.